CHALLENGES IN FULFILLING THE POLITICAL RIGHTS OF INDONESIAN MIGRANT WORKERS IN TAIWAN: A CASE STUDY FOR THE 2024 GENERAL ELECTION - Kusuma, Ardli Johan; Saraswati, Dini Putri; Satrio, Jati (Universitas Padjadjaran, 2026)
Political rights are part of human rights guaranteed by international law and the Indonesian constitution. However, Indonesian migrant workers (PMIs) in Taiwan face various challenges in exercising their right to vote in the 2024 elections. This research analyzes the obstacles faced by PMIs in Taiwan in the democratic process using politic of citizenship framework by Stokke. The research method used is a qualitative approach with semi-structured interviews with various relevant stakeholders. The results of this study show that the main obstacles to the implementation of elections for migrant workers in Taiwan are limited access to election information, differences in regulations related to voting mechanisms, and administrative challenges due to the lack of diplomatic relations between Indonesia and Taiwan. The Indonesian Migrant Workers Union (SBMI) and community organizations have an important role in fighting for the political rights of PMIs by providing political education, administrative assistance, and advocacy for the political rights of PMIs in Taiwan. This research confirms the need for better coordination between the government, trade unions, and community organizations to strengthen the protection of PMIs’ political rights.